2016
DOI: 10.5539/jas.v8n7p80
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Heterosis for Grain Yield and Rust Resistance in Pearl Millet

Abstract: Pearl millet is a dual-purpose crop in semi-arid zones of Uganda. However, no studies have been conducted to determine the gene effects for yield and yield-related traits and rust resistance in these environments; yet this knowledge is important in improving grain yield and rust resistance. A North Carolina II mating design was adopted to study the genetic effects for rust resistance and yield-related traits of improved pearl millet genotypes. The experimental design to study the objectives was alpha in two [l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…843-22A x 132R for plant height, flag leaf width, fresh biomass, harvest index and 1000 seed weight. Singh and Sharma [16], Eldie et al, [17], Siddique et al, [18], Gavali et al, [19] and Ladumor et al, [13] also reported some specific combiners for yield and its contributing characters in pearl millet.…”
Section: Gca and Sca Effectsmentioning
confidence: 97%
“…843-22A x 132R for plant height, flag leaf width, fresh biomass, harvest index and 1000 seed weight. Singh and Sharma [16], Eldie et al, [17], Siddique et al, [18], Gavali et al, [19] and Ladumor et al, [13] also reported some specific combiners for yield and its contributing characters in pearl millet.…”
Section: Gca and Sca Effectsmentioning
confidence: 97%